2019
DOI: 10.24996/ijs.2019.60.9.3
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Critical Period of Cyper-diforce® Treatment against Arthropod fauna and Productivity of Watermelon

Abstract: Watermelon has been reported to be vulnerable to insect pest pressure throughout its growth stages with a resultant indiscriminate calendar-based insecticide application (of up to 25 sprays/season in the study area), with its attendant consequences. In order to recommend the crop growth period(s) to effect chemical control measures that will give better return on investment, field trials were set-up in the early- and late-cropping seasons of 2016 and 2017. Forty, 5m long x 8m wide plots were demarcated in rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…These data also revealed that an increase in the storage period does not necessarily lead to an increase in population density. The environmental impact on insects when they compete, it becomes clear that the difference in the population density occurs as a result of the positive or negative effect of temperature and for different periods (Okrikata and Ogunwolu, 2019). A study of the biology of T. granarium described its survival as an invasive species, finding that temperature seriously affects population growth.…”
Section: Resultsmentioning
confidence: 99%
“…These data also revealed that an increase in the storage period does not necessarily lead to an increase in population density. The environmental impact on insects when they compete, it becomes clear that the difference in the population density occurs as a result of the positive or negative effect of temperature and for different periods (Okrikata and Ogunwolu, 2019). A study of the biology of T. granarium described its survival as an invasive species, finding that temperature seriously affects population growth.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, to suppress the impact of pathogen and weed pests; a broad spectrum preventive fungicide; Mancozeb 80% WP. (Zeb-care ® ) which has a contact mode of action was applied at the rate of 2 kgha -1 at the vegetative, flowering and fruiting stages and, when necessary, weeding was done manually following the method described by Okrikata and Ogunwolu 14 .…”
Section: Materials and Methods: Study Site Field Layout And Managementmentioning
confidence: 99%
“…were sampled using a 15 x 15cm yellow sticky board waved across the 5 m length of the middle row of each plot on shaking the plants as described by Okrikata and Ogunwolu 14 . Estimates of population density of aphids (Aphis gossypii Glove) were made by assessing the colony size on 12 randomly selected leaves/plot using a scale from 0 -9 as described by Okrikata nad Ogunwolu 14 . Similarly, fruits infested by fruit fly were isolated and counted in each plot.…”
Section: Assessment Of Insect Populationmentioning
confidence: 99%
See 1 more Smart Citation